2020
DOI: 10.20961/jas.v9i2.44436
|View full text |Cite
|
Sign up to set email alerts
|

Life Story of Patient With Supervision’s Fighting Against Covid-19 in Surakarta Indonesia

Abstract: <p><em>Life story of Covid-19 survivors aims to educate the people through patients’ testimony about experience with Covid-19 infection symptoms and the treatment they got in Surakarta Indonesia. The qualitative research with this biographic approach was conducted based on life story of Patients with Supervision (Pasien Dalam Pengawasan / PDP) using purposive sampling technique, so that the informants selected were PDP recovered from Covid-19, PDP’s family, friend, neighbor, Surakarta people, Pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
1
0
2
Order By: Relevance
“…A study by Dermatoto et al (2020) on the spiritual experience felt by patients with COVID-19 suggested that when they interacted with God, they placed hope and confidence in healing that only with God's permission could they recover. 30 A previous study showed that during treatment in the ICU, praying reduced anxiety and created positive thoughts. 31 Therefore, interacting with God and staying connected with the family are also important to boost the energy, which is imperative for the healing process of patients with critical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dermatoto et al (2020) on the spiritual experience felt by patients with COVID-19 suggested that when they interacted with God, they placed hope and confidence in healing that only with God's permission could they recover. 30 A previous study showed that during treatment in the ICU, praying reduced anxiety and created positive thoughts. 31 Therefore, interacting with God and staying connected with the family are also important to boost the energy, which is imperative for the healing process of patients with critical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Gejala yang timbul akibat terinfeksi Covid-19 pada setiap individu berbeda-beda. Beberapa gejala yang umum terjadi yaitu demam, batuk, sesak nafas, diare akan tetapi sebagian lainnya tidak menunjukkan tanda dan gejala sama sekali meskipun telah terinfeksi sehingga hal ini membuat penularan virus tidak disadari (Demartoto et al, 2020). Berbagai upaya dilakukan untuk pencegahan dan manajemen protokol kesehatan untuk mengatasi penularan virus yang terus berkembang (Sahoo et al, 2020).…”
Section: Pendahuluanunclassified
“…Masjid ini mempunyai lokasi diseberang jalan raya, setiap harinya banyak orang dari luar daerah yang singgah untuk beristirhat dan melaksanakan sholat.. Untuk itu penting untuk selalu menjaga kebersihan tempat ibadah. Kebutuhan spiritual diperlukan sebagai upaya pemenuhan kebutuhan selama pandemi (Demartoto et al, 2020).…”
unclassified